Aktualisasi Kearifan Lokal Marsisarian di Kota Tarutung sebagai Dasar Moderasi Beragama - Gideon Hasiholan Sitorus (Ideas Publishing, 2022)
The actualization of the essence of local wisdom as well as marsisarian has experienced a shift in function by the presence of various Western concepts due to globalization in realizing religious moderation. The purpose of this study is to describe the essence and existence of local wisdom in Tarutung City, namely marsisarian as a preventive measure as well as a discourse in seeking social harmony that can overcome conflicts amidst differences. Using the descriptive qualitative research method and the concept of individual interaction from Martin Buber as an analytical tool, this article closes with the construction of the marsisarian as the basis for religious moderation. This study shows the results, that religious moderation can be achieved in Tarutung City is the actualization of local wisdom, marsisarian which is able to suppress the rise of single narratives. Local wisdom that exists in Indonesia must be used as a basis for creating harmony because it is a social wealth that contains moral, ethical and spiritual messages.